“To write my autobiography and get myself in focus genetically”: G. Stanley Hall’s Senescence (1922) - Carney, Gemma; Hannan, Leonie (Age, Culture, Humanities: An Interdisciplinary Journal, 2021)
In this paper, we analyze G. Stanley Hall’s Senescence: The Last Half of Life (1922) as a personal narrative and scientific account of aging in the long nineteenth century. We approach the text with a critical perspective on the decline narrative in aging studies, but also by engaging with Hall’s narrative in the form of life review. Our analysis is contextualized by a historical perspective on Hall’s academic career, his views on women, and his Social Darwinism. We focus on three main narratives—embodied aging and delaying decline, old age as personal experience and a category for social analysis, and the emergence of retirement as a socioeconomic institution. In doing so, we contextualize Hall’s work by attending to the social and intellectual currents of this time. We observe the enduring influence of narratives of aging in the nineteenth century, particularly the underlying assumption of Senescence—that aging equals decline and loss, which still holds sway in mainstream gerontology research today. We argue that Senescence offers the reader a complex and often meandering narrative which reveals the experience of male aging in the long nineteenth century as well as scientific thinking on aging at the time. We conclude that Hall shows us that old age (and death) are part of life, and that as much can be learned from the experience of living through old age as can be gleaned from academic studies of social statistics or physiological decline.